Necrotizing fasciitis due to Streptococcus mitis caused by accidental human bite - Bastug, Aliye; Kislak, Sumeyye; Mutlu, Nevzat Mehmet; Akcaboy, Zeynep Nur; Koksal, Asude; Sertcelik, Ahmet; Ünlü, Ramazan Erkin; Akinci, Esragul; Bodur, Hurrem (The Journal of Infection in Developing Countries, 2016)
Human bite wounds are more prone to infection than animal bites, which may cause necrotizing soft tissue infections such as myositis, fasciitis. Both aerobic and anaerobic microorganisms may be responsible, including Streptococcus spp., Staphylococcus aureus, Peptostreptococcus spp. Necrotizing fasciitis is characterized by serious tissue destruction and systemic toxicity with high morbidity and mortality. We report a patient with Streptococcus mitis associated necrotizing fasciitis on the upper extremity resulting from an accidental human bite, which caused nearly fatal infection. Prophylactic antibiotic treatment should be given after a human bite to prevent infection. If the infection signs and symptoms develop, rapid diagnosis, appropriate antibiotic and surgical therapy should be administered immediately. Streptococcus mitis is a viridans streptococcus, usually known as a relatively benign oral streptococcus. To our knowledge, this is the first necrotizing fasciitis case due to Streptococcus mitis after human bite.